A política da salvação: a política e o encantamento da Igreja Universal do Reino de Deus em Cáceres MT - Cuyabano, Felippe Otávio de Souza (2009)
The present dissertation has as its aim analyse the political participation of the church "Igreja Universal do Reino de Deus" (IURD) in Cáceres - Mato Grosso, particularly in the election periods from 2002 to 2008. Despite the significance given by various studies to IURD acting as an important phenomenon in the Brazilian religious field, this analysis is developed from IURD´s role in using socio-religious practises for the formation of followers into electors. The theoretic-methodologic course is attatched, especially, with Weber and Pierre Bourdieu´s reflections, inspiring the analysis of free interviews, documental soucers, participant observation, and memory, during work field incursion, considering the followers as research subjetcs of the obtained data consolidation. This relation between the followers and the church enables a comprehension of how the transformation from follower to elector is given, in a conjuncture joining the religious and political speeches in an environment that concentrates various existing social conditions and in an activity organized by the church regarding its candidates. Thus, joining,altogether, the theoretical presupposition, the qualitative research based in bibliographies regarding the theme, newspapers, magazines and publications. Searching, in a long-term process, how IURD used the political speech as a symbolic element for the formation of "God´s politics". The religion, soon started to be ranked as a tool for citizenship and moral formation, whose use demanded the implementation of the church representatives candidature. In the context of Cáceres and Mato Grosso, we looked to analyse how the iurdian hierarchy actions were formed, the engerderment of institutional political-religious practises and individual electoral profiles formation regarding the participation of IURD in the municipality elections